2020
DOI: 10.34314/jalca.v115i12.4203
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Sensitive Agents for Making Stimuli Responsive Leathers

Abstract: Herein, we report the synthesis and application of a smart polymeric acrylic syntan (synthetic tanning material), which can respond to temperature and pH. Behavior of polymer at different pH (1-10) at room temperature (28°C) was studied. Also interactions with collagen were ascertained in order to understand the polymers’ response towards secondary structures of collagen. Leather made using the experimental syntan demonstrated higher temperature resistance of 3±0.5°C compared to control syntan treated leathers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 0 publications
2
5
0
Order By: Relevance
“…The traction of Nile tilapia leather regions did not influence the strength (Table 1), while for tearing, tail region showed lower strength 49.65 N mm -1 and head and central regions did not show a significant difference between them, whose average was 61.49 N mm -1 (p <0.05). These results corroborate Alla et al 14 who evaluated Nile tilapia leathers in relation to two regions (head and hindquarters) and three leather directions (longitudinal, transverse and diagonal). The author also reported that the analyzed region did not influence the tensile strength of the leather, whose average value was 12 N mm -2 , lower than that of this test 13.46 N mm -2 (p <0.05).…”
Section: Test 1: Physicomechanical Characteristicssupporting
confidence: 91%
See 4 more Smart Citations
“…The traction of Nile tilapia leather regions did not influence the strength (Table 1), while for tearing, tail region showed lower strength 49.65 N mm -1 and head and central regions did not show a significant difference between them, whose average was 61.49 N mm -1 (p <0.05). These results corroborate Alla et al 14 who evaluated Nile tilapia leathers in relation to two regions (head and hindquarters) and three leather directions (longitudinal, transverse and diagonal). The author also reported that the analyzed region did not influence the tensile strength of the leather, whose average value was 12 N mm -2 , lower than that of this test 13.46 N mm -2 (p <0.05).…”
Section: Test 1: Physicomechanical Characteristicssupporting
confidence: 91%
“…The author also reported that the analyzed region did not influence the tensile strength of the leather, whose average value was 12 N mm -2 , lower than that of this test 13.46 N mm -2 (p <0.05). For direction of removal of the specimens, the results were similar to those of this test as well, due to diagonal direction, according to Alla et al 14 have shown lower strength 6.80 N mm -2 and longitudinal and transversal higher strength values, although shown no difference between them, whose average value was 15.20 N mm -2 , being higher than that of this test 14.49 N mm -2 This seems to be related to distribution of collagen fibers in the leather. Everything indicates that in the longitudinal direction it has a smaller number of fine fibers (reticulin), and these are intended to assist in tying collagen fibers and providing resistance in progressive tearing.…”
Section: Test 1: Physicomechanical Characteristicssupporting
confidence: 84%
See 3 more Smart Citations